A Clinical and Pathological Variant of Acute Transplant Glomerulopathy - Miklos Z. Molnar; G. V. Ramesh Prasad; Darren A. Yuen; Serge Jothy; Jeffrey S. Zaltzman (Case Reports in Pathology)
Acute transplant glomerulopathy transplant glomerulopathy (TG) is a common cause of late renal allograft loss. We describe a unique case of a renal transplant recipient who developed rapid-onset nephrotic-range proteinuria and acute kidney injury secondary to C4d negative acute TG. Two courses of intravenous Rituximab resulted in significant improvement in proteinuria and allograft function. In the setting of acute nephrotic-range proteinuria postrenal allograft, both renal biopsy with electron microscopy and screening for de novo donor-specific antibody should be performed to distinguish atypical presentations of TG from other diagnoses.